Use of a User-Friendly Tablet Application to Communicate with Pediatric Patients on Mechanical Ventilators - Chanita Tantacharoenrat; Tassanee Prasopkittikun; Somsiri Rungamornrat; Kawewan Limprayoon (Universidad de La Sabana, 2018)
Uso de una aplicación user-friendly para tableta en la comunicación con pacientes pediátricos sometidos a respirador artificial Uso de um aplicativo para tablet fácil de usar para comunicação com pacientes pediátricos em ventilação mecânica Objectives: To examine the effect of using a tablet application as a communication aid with mechanically ventilated pediatric patients on communication satisfaction of nursing staff and caregiver-patient dyads. Materials and method: The one-group pretest-posttest design was used to examine communication satisfaction for the nursing staff, and a nonequivalent pretest-posttest control group design was used for caregivers. The sample comprised 44 nursing staff and 18 dyads of caregivers and the ventilated pediatric patients from two hospitals in Thailand. A paired t-test was used for comparison of nursing staff, the Mann-Whitney U test for comparison of caregivers, and descriptive statistics to describe the children's satisfaction. Results: The nursing staff was more satisfied with communication using the tablet application than regular communication methods (t = -9.13, df = 43, p < .001). Caregivers who used the tablet application also reported more communication satisfaction, compared to those who used regular communication methods (U = -3.41, p < .001). Nearly 90% of the pediatric patients reported being completely satisfied with the use of the application. Conclusions: The tablet application designed for facilitating communication with mechanically ventilated pediatric patients improved communication satisfaction. It should be encouraged as one of the assistive communication devices for wide use.